Microfluidic Concentric Gradient Generator Design for High-Throughput Cell-Based Studies - Ezra Tsur, Elishai; Zimerman, Michal; Maor, Idan; Elrich, Avner; Nahmias, Yaakov (Frontiers in Bioengineering and Biotechnology, 2017)
Gradients of diffusible signaling molecules play important role in various processes, ranging from cell differentiation to toxicological evaluation. Microfluidic technology provides an accurate control of tempo-spatial conditions. However, current microfluidic designs are lacking when needed to handle multiple gradients and cell populations simultaneously. Here we demonstrate a rapidly adapting microfluidic design able to expose different cell lines to an array of chemical gradients. Our design is based on pressure-equilibrated concentric channels and a pressure dissipating control layer, facilitating a capability to seed different cell populations in a single device. The design was numerically evaluated and experimentally validated. The device consists of 8 radiating stimuli channels and 12 circular cell culture channels, creating an array of 96 different continuous gradients that can be simultaneously monitored over time.